2014
DOI: 10.5194/acp-14-5057-2014
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and sources of coastal marine aerosol particles during the 2008 VOCALS-REx campaign

Abstract: Abstract. The chemical composition of aerosol particles (Dp ≤ 1.5 μm) was measured over the southeast Pacific Ocean during the VAMOS (Variability of the American Monsoon Systems) Ocean-Cloud-Atmosphere-Land Study Regional Experiment (VOCALS-Rex) between 16 October and 15 November 2008 using the US Department of Energy (DOE) G-1 aircraft. The objective of these flights was to gain an understanding of the sources and evolution of these aerosols, and of how they interact with the marine stratus cloud layer that p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The sulfate consistently showed a higher loading near the surface within the MBL and decreased loadings with altitude for profiles of all air mass types. The AMS-derived ammonium and sulfate loadings (NH 4 and SO 4 ) had an equivalent ratio of 1.5-2 for most of the SLRs; highly acidic sulfate was also previously observed along the western coast of South America (Lee et al, 2014). There were some SLRs with relatively high sulfate and hematite loadings during SA + SD air masses.…”
Section: The Hematite Content Of Dust Aerosolsupporting
confidence: 61%
“…The sulfate consistently showed a higher loading near the surface within the MBL and decreased loadings with altitude for profiles of all air mass types. The AMS-derived ammonium and sulfate loadings (NH 4 and SO 4 ) had an equivalent ratio of 1.5-2 for most of the SLRs; highly acidic sulfate was also previously observed along the western coast of South America (Lee et al, 2014). There were some SLRs with relatively high sulfate and hematite loadings during SA + SD air masses.…”
Section: The Hematite Content Of Dust Aerosolsupporting
confidence: 61%
“…The transport is substantial during the dry season and thus, the aerosols very likely contain a large fraction of BC and organic carbon (OC) which is characteristic of biomass burning. Allen et al [2011] and Lee et al [2014] reported large amounts of organic aerosols simultaneously with increased CO concentration in the remote FT over the southeast Pacific Ocean and suggested that the aerosols were long-range transported from continental sources. In agreement with our findings, Freitag et al [2014] reported that air masses over the Pacific could be transported from 80 ∘ W to 120 ∘ W and also from the upper to the lower FT.…”
Section: Discussionmentioning
confidence: 99%
“…However, anthropogenic aerosols may also be present, in particular, during biomass burning periods [Clarke and Kapustin, 2010]. Lee et al [2014] found in their measurements near the South American coast in October and November 2008 that the MBL was dominated by sea salt, sulfate, and organic aerosols, where the sulfate and organics were mostly of continental origin.…”
Section: Introductionmentioning
confidence: 99%
“…Aircraft observations of marine stratocumulus clouds showed that the vertical profile of LWC is essentially the same as the adiabatic profile; i.e., the cloud is almost adiabatic (Keil and Haywood, 2003). Furthermore, it remains unclear whether the subsequent entrainment-mixing mechanism is predominantly homogeneous, inhomogeneous, or in between (Andrejczuk et al, 2009;Lehmann et al, 2009). Some previous studies have shown that stratocumulus is generally dominated by the inhomogeneous mechanism (Pawlowska et al, 2000;Burnet and Brenguier, 2007;Haman et al, 2007;Lu et al, 2011;Yum et al, 2015).…”
Section: Entrainment In Stratocumulusmentioning
confidence: 99%